RELASI MANUSIA DAN LINGKUNGAN DALAM NOVEL TANJUNG KEMARAU KARYA ROYYAN JULIAN (KAJIAN EKOKRITIK SASTRA) - Alam, Syamsu (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
Human and Environmental Relations in the Novel Tanjung Kemarau by Royyan Julian (Literary Ecocritic Study). This study aims to describe the form of environmental damage and the form of human relations with the environment based on the ecocritical study of the novel Tanjung Kemarau by Royyan Julian. The results of this study indicate: 1) The relationship between characters and the environment in the novel Tanjung Kemarau is a picture of the reciprocal relationship between the characters and the natural environment by doing positive things in the natural environment, 2) The form of environmental damage in the novel Tanjung Kemarau is a description of how environmental damage is caused by human activity.